Phylogenetic Systematics of the Water Toad (Bufo stejnegeri) Elucidates the Evolution of Semi-aquatic Toad Ecology and Pleistocene Glacial Refugia - Fong, Jonathan J.; Yang, Bao-Tian; Li, Pi-Peng; Waldman, Bruce; Min, Mi-Sook (Frontiers in Ecology and Evolution, 2020)
The water toad (Bufo stejnegeri) is endemic to Northeastern Asia (South Korea, North Korea, and China) and has unique ecology for a toad by being semi-aquatic and breeding in lotic environments. We use a suite of phylogenetic analyses to understand the evolution of B. stejnegeri’s distinctive ecology and the impact of Pleistocene glacial cycles on the biodiversity of Northeast Asia. For the evolution of a semi-aquatic lifestyle, although B. stejnegeri is closely related to two other semi-aquatic Bufo species (B. torrenticola and B. andrewsi), ancestral state reconstruction analysis infers an independent evolution in all three species. Upon closer inspection, B. stejnegeri exhibits major differences in amplexus and egg-laying behaviour compared to the other two species, supporting independent evolution. Divergence dating analyses infer B. stejnegeri to have originated during the Late Miocene-Early Pliocene (4.3 Ma, 2.7–6.2 Ma). This species does not exhibit population differentiation with respect to mountain range, but shows a genetic pattern of southern richness and northern purity supporting a single refugium in Korea during Pleistocene glacial cycles. The Bayesian skyline plot supports this inference, inferring a population decline followed by expansion during the Pleistocene. Although not as species rich as the tropics, we hope this study helps spark interest in Northeast Asian biodiversity.